Surface disinfection by UV & effect of repetitive organisms exposure on self disinfecting chemicals - Tan, Li Yan (Nanyang Technological University, 2022)
Globalization refers to a growing in independency of the world’s economies, cultures and populations which is achieved via cross border trade in goods and service, advanced technology, increased investment, people and also information. In addition to these, globalization has also enhanced the growth of global food supply chain. With improved accessibility, food from around the world can be enjoyed by everyone without the hassle of traveling to the country. However, with the expansion of food supply chain, many growing concerns of food safety has been faced. Food transported around the world become more vulnerable to infectious diseases and pathogens. One of the most recent infectious disease outbreaks is Covid-19. Covid-19 has caused healthcare systems and global food supply chains to be strained. Thus, awareness of the safety and efficiency of food management systems should be considered in preventing the spread of infectious diseases. This study aims to use Ultra-Violet rays as a disinfection pre-treatment in minimizing virus transmission in food packaging in Singapore. Through this study, different Ultra Violet LED UVC lamps will be used as a surface disinfectant to minimize the pathogen spread via the food packaging. The food packaging film will contain contaminant with laboratory bacteria grown E-coli. The wavelength of 254nm will be kept constant throughout the experiment and disinfection will take place under 3 different exposure distances ranging from 6cm to 12cm with varying timing from 0 to 25 minutes. The study has found out that disinfection can be carried out effectively when the bacteria is the exponential growth phase and that maximum disinfection can be achieved by using the highest power with shortest distance from the lamp to the bacteria sample. Furthermore, SEM analysis revealed negligible damage to the packaging after exposure to UV radiation within a 30 minutes duration.